(untitled) (Journal of Engineering, 2013)
The construction of embankment for roadway interchange system at urban area is restricted due to the large geometry requirements, since the value of land required for such construction is high, and the area available is limited as compared to rural area. One of the optimum solutions to such problem is the earth reinforcement technique which requires a limited area for embankment construction. Gypseous soil from Al-Anbar governorate area was obtained and subjected to various physical and chemical analysis to determine it is properties. A laboratory model box of 50x50x25 cm was used as a representative embankment; soil has been compacted in five layers at maximum dry density (modified compaction) and an aluminum reinforcement strips were introduced between layers. The model was subjected to cyclic loading and the vertical and lateral deformations were detected at different stages of loading cycles using LVDT. The reinforced soil embankment under soaking condition exhibited vertical settlement at the top surface was (12.55 mm) while the lateral displacements at (1st, 3rd layer) were (2.18, 1.32) mm respectively at (47 load cycles).For reinforced gypseous soil, embankment without soaking cured for 24 hours, the Number of load cycles was found to be (165) loading cycles with vertical displacement (9.12 mm), that means an improvement of 59%. Accordingly, the lateral displacement in 1st and 3rd layers were (3.28, 2.59) mm respectively which observes improvement by (28% and 5%) respectively. The rates of improvement are taken with respect to the reinforced pure dry soil sample.